2020
DOI: 10.3390/ijms21031071
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Chondrocytes in Rheumatoid Arthritis: The Chicken and the Egg

Abstract: Rheumatoid arthritis (RA) is one of the inflammatory joint diseases that display features of articular cartilage destruction. The underlying disturbance results from immune dysregulation that directly and indirectly influence chondrocyte physiology. In the last years, significant evidence inferred from studies in vitro and in the animal model offered a more holistic vision of chondrocytes in RA. Chondrocytes, despite being one of injured cells in RA, also undergo molecular alterations to actively participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 120 publications
(134 reference statements)
0
32
0
Order By: Relevance
“…However, NSAIDs have serious side effects such as stomach ulcers and do not block the synthesis of pro-inflammatory factors and proteins, which then further promote the breakdown of articular cartilage. This underlines the need for anti-inflammatory therapy, which on the one hand inhibits COX-2 (and thus prostaglandin synthesis) but on the other hand may modulate chondrocytes metabolism, further blocking progressive joint degeneration [131,132]. In fact, Subbaramaiah and co-workers demonstrated that resveratrol is a potential COX-2 inhibitor and the administration of resveratrol inhibited COX-2 expression and thus the production of PGE 2 [133].…”
Section: Resveratrolmentioning
confidence: 99%
“…However, NSAIDs have serious side effects such as stomach ulcers and do not block the synthesis of pro-inflammatory factors and proteins, which then further promote the breakdown of articular cartilage. This underlines the need for anti-inflammatory therapy, which on the one hand inhibits COX-2 (and thus prostaglandin synthesis) but on the other hand may modulate chondrocytes metabolism, further blocking progressive joint degeneration [131,132]. In fact, Subbaramaiah and co-workers demonstrated that resveratrol is a potential COX-2 inhibitor and the administration of resveratrol inhibited COX-2 expression and thus the production of PGE 2 [133].…”
Section: Resveratrolmentioning
confidence: 99%
“…6 b). As the sole producers of cartilaginous matrix and as mediators of inflammation, chondrocytes represent an important future cellular target for therapy in RA as well as osteoarthritis [ 44 46 ]. Chondrocytes have been a relatively overlooked target in fluorescence imaging approaches for RA, which have typically focused on inflammatory cells such as macrophages [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important point to note is that cartilage participates in both inflammatory and bone destruction phases (34). Chondrocytes are only resident cells in the cartilage, which not only act as target cells of inflammatory mediators, but also serve as effector cells and play an important role in cytokine cascades (15,(35)(36)(37)(38). Insights into the cascades between chondrocytes and cartilagereactive T cells could be helpful to find new biological markers and therapeutic targets of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%